Bullying in the library workplace - Kim, Hak Joon; Geary, Carol Anne; Bielefield, Arlene (Library Leadership & Management, 2018)
The primary purposes of the study were to investigate how often bullying occurs in libraries and whether bullying policies exist in libraries. The first survey questionnaire was sent to library personnel in the six New England states through statewide email distribution lists. Altogether 571 library staff members completed the survey. The second survey questionnaire was sent to large public and academic libraries in New England to see if they have anti-bullying policies in the workplace. The results of the study clearly showed there were significant reports of workplace bullying in all kinds of libraries. Nonetheless, not many libraries have policies that deal with this workplace challenge.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/185-409-335-946-838, pop00227 tex.type: [object Object]
Keywords: bullying; bullying polices; dept.ils; library policies; workplace bullying